2002
DOI: 10.1007/s00415-002-1205-3
|View full text |Cite
|
Sign up to set email alerts
|

Initial therapy for Parkinson's disease: levodopa vs. dopamine receptor agonists

Abstract: Levodopa therapy is essential for patients in the advanced stages of Parkinson's disease. However, at early stages, DA agonist therapy has similar efficacy in the treatment of parkinsonism and a lower incidence of motor complications compared to levodopa therapy several years after the initiation of the therapy. The main factors causing motor complications have been speculated to be a severe reduction of dopaminergic nerve terminals because of disease progression, and a pulsatile stimulation of DA receptors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Non-ergot DAs (apomorphine, piribedil, pramipexole, ropinirole and rotigotine) seem to possess a very low and statistically insignificant risk of fibrotic complications and are preferred in clinical practice [131]. Potential benefits of DAs are related to their longer bioavailability in the synaptic cleft leading to equalised L-Dopa/DC inhibitor stimulation of dopaminergic terminals in the striatum [132].…”
Section: Second-line Treatment Drug Treatmentmentioning
confidence: 99%
“…Non-ergot DAs (apomorphine, piribedil, pramipexole, ropinirole and rotigotine) seem to possess a very low and statistically insignificant risk of fibrotic complications and are preferred in clinical practice [131]. Potential benefits of DAs are related to their longer bioavailability in the synaptic cleft leading to equalised L-Dopa/DC inhibitor stimulation of dopaminergic terminals in the striatum [132].…”
Section: Second-line Treatment Drug Treatmentmentioning
confidence: 99%
“…This difference cannot be attributed to medication, since it is not necessary to withdraw PD medication to measure DAT levels with SPECT 13. Moreover, previous reports have suggested that dopaminergical agonist therapy14 that are more commonly used in EOPD might reduce DAT loss during PD disease progression. Although EOPD patients had lower DAT density, they presented similar motors symptoms disability and PD severity at off state.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to treatment, EOPD patients have a better medication response to levodopa (Ribeiro et al, 2009 ). Moreover, Kondo et al have suggested that the dopamine agonist therapies that are more commonly used in EOPD might reduce dopamine transporter (DAT) loss during PD disease progression (Kondo, 2002 ). The pathophysiological mechanisms that differentiate EOPD and LOPD disease progression are not yet clear (Shih et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%